Analysis of UTBK Tryout Performance: Insights into Student Readiness Across Mathematical and Language Competencies - Sarumaha, Eklesya; Pakpahan, Elisda; Lestari, Nadya Ayu; Falah, Siti Nurul; Amelia, Zefani; Daulay, Rabiah Afifah (META: Journal of Science and Technological Education, 2024)
The UTBK (Computer Based Written Exam) serves as a pivotal examination for Indonesian students seeking entry to state universities. This study analyzes tryout performance conducted by Laras Bimbel to evaluate participants' readiness for UTBK 2024. Employing a quantitative methodology, data were collected through offline tryouts integrated with digital platforms. Participants' scores, time management, and error patterns were examined to assess the distribution of competencies across sub-materials, particularly mathematical reasoning and literacy. Results reveal significant variations in performance, highlighting the need for tailored preparation strategies. This research underscores the importance of innovative educational interventions to address areas of difficulty, thereby enhancing students' overall exam preparedness.